(untitled) (Anclajes, 2018)
Residing in Germany since 1978, Andrea Pagni, Argentine researcher and expert on literary translation studies, discusses her current research in this field and offers a review of her approach to translation studies. In an interview at the University of Erlangen-Nürnberg (FAU), where she has been Professor of Latin American Literature and Culture since 2005, she reflects on the status of translation in cultural journals, the confluence between translation and genre, post-monolingualism, and its role as a “writing laboratory” in the shaping of cultural systems.